Trichomonas vaginalis as a rare cause of male factor infertility at a hospital in East Anatolia - Ozdemir, E.; Kelestemur, N.; Kaplan, M. (Wiley-Blackwell, 2011)
Trichomonas vaginalis is known as an important cause of sexually transmitted infection in developing countries. The prevalence and spectrum of Trichomonasis in men are less characterised. We analysed the presence of T. vaginalis in 80 infertile men using wet mount microscopy, Giemsa staining, culture and PCR methods. We found 2.5% positivity for T. vaginalis using PCR method. Wet mount microscopy was ineffective. Giemsa staining and culture tests were positive only in one patient. Both of our PCR-positive patients were symptomatic. Our findings suggest that T. vaginalis should be considered for the aetiology of male factor infertility, although it is rare in developed countries.
Keywords: Male factor infertility; semen PCR; sexually transmitted diseases; Trichomonas vaginalis